Enhancing Security using Video Steganography and WaterMarking - Harinath, Depavath; Babu, K. Ramesh; Satyanarayana, P.; Murthy, M.V. Ramana (European Journal of Applied Sciences, 2015)
The rapid development of data transfer through internet made easier to send the data accurate and faster to the destination. Besides this, anyone can modify and misuse the valuable information through hacking. Steganography attempts to hide the secret information and make communication undetectable. Steganography is used to conceal the secret information so that no one can sense the information. Steganographic method has many challenges such as high hiding capacity and imperceptibility. This paper presents Video Steganography with digital watermarking techniques as an efficient and robust tool for protection.